Penerapan Metode Analytical Hierarchy Proces (AHP) untuk menentukan Kriteria Hutan Kota Fungsi Rekreasi untuk Masyarakat Perkotaan - Dyah Permata, Nike (JURNAL RUANG / ISSN : 2085-6962, 2024)
Urban forests as green open spaces provide ecological, recreational, and aesthetic benefits. This study aims to determine the criteria for urban forests as recreational areas for urban communities. The steps taken include analyzing evaluation criteria and establishing standard criteria using the Analytical Hierarchy Process (AHP) method to determine the weight of the criteria. The results of the calculations show that the component criteria obtained are management (%), urban forest objects (%), visitors (%), accessibility (%), visitor activities (%), facilities and infrastructure (%). Therefore, the highest criteria for urban forests with recreational functions are management, and the lowest criteria are infrastructure